Imunolocalização da enzima Purina Nucleosídeo Fosforilase (PNF) em polpas de ratos expostas ao meio bucal - Tavares, Cauana Oliva (2014)
The dental pulp activates inflammatory and immunopathologic defenses owing to microorganisms. However, pulp tissue is confined by rigid walls and inflammation may perpetuate or extend pathologic alteration due to its own events. Within this context, the enzyme Purine Nucleoside Phosphorylase (PNP) is related to a chain of events that generate activated T cells, thus it becomes an interesting target for pulp inflammation control. Under these circumstances, the present study aimed to characterize the PNP enzyme in rat pulp tissue, by immunohistochemistry, as well as establish a correlation among the inflammatory events with the enzyme, by histologic methods. Eighteen animals were divided into 3 groups: group 1 (n=6) no cavity opening was performed; group 2 (n=6) pulp tissue exposure for 24 hour; group 3 (n=6) pulp tissue exposure for 7 days. Qualitative analysis was applied for histologic observations, which has indicated the same intensity of inflammation for groups 2 and 3. However, in group 3, inflammation was further extended through the pulp. The main inflammatory cells observed were neutrophils, for both experimental periods. No pathologic alterations were shown for the control group. Immunolocalization detected the presence of PNP in endothelial cells of group 3 at the transition period from acute to chronic inflammation. No PNP basal expression was observed for the groups 1 and 2. In conclusion, PNP is activated in rat pulp tissue. Our findings show a novel endodontic target and contribute with ongoing and future endodontic scientific studies that aim drugs development for pulp damage control.